Hubungan Pola Makan dengan Status Gizi pada Anak Usia Pra Sekolah di TK Taman Annisa Miruek Taman Kabupaten Aceh Besar - Putri Yani; Khaira Rizki; Nurul Amna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
. Malnutrition rates among children remain quite high, according to 2024 national statistics, which indicate that good eating habits in accordance with balanced nutritional needs are not yet ideal. Children's eating habits, dietary diversity, and parental understanding all impact their nutritional status. To promote optimal growth and development in children, it is crucial to monitor and establish appropriate eating habits from an early age. The aim of this study was to determine the relationship between eating habits and nutritional status of preschool-aged children. This study used a cross-sectional analytical design and quantitative methodology. Purposeful sampling was used to select a sample of 33 children from the 50 children in the study population. The study was conducted between September 22 and October 1, 2025. A Food Frequency Questionnaire (FFQ) was used to examine dietary patterns, while nutritional status was measured through weighing using a digital scale. Based on the findings, 22 children (66.7%) had a healthy diet, while 11 children (33.3%) had a poor diet. The Chi-Square statistical test showed a p value of 0.008 (p < 0.05), indicating a relationship between eating habits and nutritional status in preschool children at Taman Annisa Miruek Kindergarten, Aceh Besar Regency. According to balanced nutrition guidelines, parents should regularly assess their children's growth and focus more on the diversity and balance of their food intake. To improve children's nutritional status as much as possible, schools are required to collaborate with health workers to educate parents and children about nutrition.